2008
DOI: 10.1002/jssc.200700499
|View full text |Cite
|
Sign up to set email alerts
|

Application of supercritical fluid chromatography to the analysis of hydrophobic metabolites

Abstract: This review describes the usefulness of supercritical fluid chromatography (SFC) in the analysis of hydrophobic metabolites. The use of SFC for the analysis of naturally occurring polyprenols markedly improves the chromatographic resolution of polyprenol homologues and their geometric isomers as compared to conventional HPLC. Under optimized SFC conditions, individual homologues with 10-100-mers were separated. Furthermore, we established an analytical system for the fingerprinting and profiling of diverse lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…However, the addition of a co‐solvent substantially increases the critical values of carbon dioxide . Column efficiencies obtained in SFC are comparable to those obtained in HPLC with identical particle size, but they are obtained in SFC at linear velocities that are three to five times greater than in HPLC . These advantages make SFC an advantageous separation technique that is widely used in the pharmaceutical industry for achiral and chiral separations on both analytic and preparative scales.…”
Section: Introductionmentioning
confidence: 94%
“…However, the addition of a co‐solvent substantially increases the critical values of carbon dioxide . Column efficiencies obtained in SFC are comparable to those obtained in HPLC with identical particle size, but they are obtained in SFC at linear velocities that are three to five times greater than in HPLC . These advantages make SFC an advantageous separation technique that is widely used in the pharmaceutical industry for achiral and chiral separations on both analytic and preparative scales.…”
Section: Introductionmentioning
confidence: 94%
“…Another analytical method is supercritical fluid chromatography (SFC). It has been reported that the sensitivity of SFC was higher than that in LC, and several structural isomers that could not be separated by LC were successfully separated using SFC [31][32][33][34][35]. However, SFC also has several disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we developed a low‐temperature HPLC using liquid CO 2 as the mobile phase prior to ultra‐low‐temperature HPLC. It is well known that CO 2 is often used as the mobile phase of SFC . However, SFC separations are generally performed in a critical condition, i.e.…”
Section: Introductionmentioning
confidence: 99%